2(3c-1)-4=4c+2

Simple and best practice solution for 2(3c-1)-4=4c+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(3c-1)-4=4c+2 equation:


Simplifying
2(3c + -1) + -4 = 4c + 2

Reorder the terms:
2(-1 + 3c) + -4 = 4c + 2
(-1 * 2 + 3c * 2) + -4 = 4c + 2
(-2 + 6c) + -4 = 4c + 2

Reorder the terms:
-2 + -4 + 6c = 4c + 2

Combine like terms: -2 + -4 = -6
-6 + 6c = 4c + 2

Reorder the terms:
-6 + 6c = 2 + 4c

Solving
-6 + 6c = 2 + 4c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-4c' to each side of the equation.
-6 + 6c + -4c = 2 + 4c + -4c

Combine like terms: 6c + -4c = 2c
-6 + 2c = 2 + 4c + -4c

Combine like terms: 4c + -4c = 0
-6 + 2c = 2 + 0
-6 + 2c = 2

Add '6' to each side of the equation.
-6 + 6 + 2c = 2 + 6

Combine like terms: -6 + 6 = 0
0 + 2c = 2 + 6
2c = 2 + 6

Combine like terms: 2 + 6 = 8
2c = 8

Divide each side by '2'.
c = 4

Simplifying
c = 4

See similar equations:

| 3m-9m=24 | | 3-2x/3=7 | | 0.9x=0.1x+0.4 | | 18x^2+9x-5=0 | | 3r^2-9r-12=0 | | -4x^2+12x+1=0 | | 0.2k-4=8 | | 0.4x+14=0.6x-1 | | -5.28+1.3a=-2.1a-a | | 11w+2w+2=5w-b | | 7(h-2/5) | | x+23+3x=-3-3x-9 | | 12x+7=-11+6x | | Y=16x^2-121y^2 | | 7(h-5/2) | | C/9+18=24 | | 31/4-15/8 | | 3b^2+2b-16=0 | | 3c+6t+b=2c+4t | | -1/4+y=-2/3 | | 225=2500*r*2 | | 10+0.5w=1/2w-10 | | 12x-13=6x | | x+(x-5)+(x+5)=360 | | 9-2*3+u=(27-24)(2)+u | | x-15=13-16x | | 0.08k-4=0.1k+8 | | 8.9+1.2(3a+1)=124.4 | | 7x-13-2x=9+5x | | F(x)=16x^2-121y^2 | | 9/4-5/6=-1/2 | | 2m+3s=1m+5s |

Equations solver categories